The influence of a hydrolysis-inhibiting additive on the degradation and biodegradation of PLA and its nanocomposites. (February 2015) - Stloukal, Petr; Kalendova, Alena; Mattausch, Hannelore; Laske, Stephan; Holzer, Clemens; Koutny, Marek
Abstract: A carbodiimide-based additive, intended to stabilize PLA based materials to avoid hydrolytic degradation during processing, was incorporated into a series of PLA and nanofiller containing PLA films. The influence of the additive on the subsequent degradability of the materials was studied under the conditions of melt processing, biodegradation in compost and abiotic hydrolysis. Identical films without the additive were used as reference materials. Adding an anti-hydrolysis agent significantly retarded the decomposition of PLA in all the degradation processes tested. Both biodegradation and the abiotic hydrolysis of the PLA-based materials investigated were substantially retarded. This effect was much less pronounced in a material with organically modified montmorillonite.